2019
DOI: 10.5455/aim.2019.27.263-267
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smartphone Applications on Patients Self-care with Hypertension: A Systematic Review Study

Abstract: Introduction: High blood pressure or hypertension is one of the chronic diseases causing other serious diseases and syndromes. Active involvement of the patient in the management of the disease is crucial in improving self-care and clinical outcomes. Mobile technology is nowadays used widely to improve the self-care process in people with chronic diseases such as hypertension. Aim: The objective of this study was to provide an overview of the existing research evaluating the impact of mobile applications on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Applications used especially by diabetic patients provide the opportunity to manage insulin need, automatic feedback on blood glucose levels and secure data sharing with healthcare providers 21 . Although the results are variable, it is reported that these applications achieve successful results in hypertensive patients 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications used especially by diabetic patients provide the opportunity to manage insulin need, automatic feedback on blood glucose levels and secure data sharing with healthcare providers 21 . Although the results are variable, it is reported that these applications achieve successful results in hypertensive patients 22 …”
Section: Discussionmentioning
confidence: 99%
“…21 Although the results are variable, it is reported that these applications achieve successful results in hypertensive patients. 22 The study has some limitations. Data were collected by selfreporting.…”
Section: Ta B L Ementioning
confidence: 98%
“…The duration of the TTM-based educational interventions used was different and at most under six months. Changing a person's behavior takes a long time, especially if the behavior has become a habit [34]. Even so, the interventions in this review were able to change the patient's behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic media is the most widely used in this review. Education using electronic media can improve self-care for hypertension patients [32,34,37] even though Internet-based mobile applications do not apply to all age levels and all different patient characteristics [30][31][32]. The method that is mostly used in this research is combined counseling and education.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the use of smartphone-based management of hypertension in the follow-up of patients with myocardial infarction did not have an effect on improved blood pressure control in the Netherlands [ 44 ]. A systematic review of the effectiveness of smartphone apps in hypertension management found mixed results across trials and may be influenced significantly by national characteristics, culture, and living and digital environments [ 45 ]. There is still a need to accumulate evidence on the usefulness of digital technology in health promotion and disease prevention/treatment, and digital healthcare is still in the process of development as an academic field.…”
Section: Challenges Emerging In the Use Of Digital In Healthcarementioning
confidence: 99%